Rational Analysis of the Utilization of Pentoxifylline in a Tertiary Hospital: Central Hospital Affiliated to Shandong First Medical University - Zheng Y; Yin Y; Liu H; Gao W; Wang Q (Risk Management and Healthcare Policy)
Yuanyuan Zheng,1,2,* Yanhui Yin,1,* Hong Liu,3 Wenwen Gao,1 Qian Wang1 1Department of Pharmacy, Central Hospital Affiliated to Shandong First Medical University, Jinan, 250013, People’s Republic of China; 2The First Affiliated Hospital of Shandong First Medical University, Jinan, 250014, People’s Republic of China; 3Department of Pharmacy, Laiwu District People’s Hospital, Jinan, 271100, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qian Wang, Department of Pharmacy, Central Hospital Affiliated to Shandong First Medical University, No. 105 Jiefang Road, Lixia District, Jinan City, Shandong Province, 252213, People’s Republic of China, Email 13165131021@163.comObjective: This study aimed to evaluate the rational use, safety, and economic implications of pentoxifylline in a hospital setting and provide recommendations for its appropriate clinical application.Methods: A retrospective analysis was conducted on 322 patients discharged from September to December 2020, who received pentoxifylline. Data were collected from the hospital information system, and the rationality of prescriptions was assessed based on drug instructions and guidelines. Adverse drug reactions (ADRs) were analyzed using CTCAE criteria. Economic evaluations included defined daily dose cost (DDDc) and incremental cost-effectiveness ratio (ICER) analyses.Results: The rational prescription rate for pentoxifylline was 38.51%, with the main irrationalities observed in indications (31.82%), dosage and usage (21.21%), contraindications (47.98%), and drug combinations (40.40%). Adverse reactions were reported in 12 cases (3.73%), primarily involving the nervous (75.00%) and digestive systems (41.67%). Most ADRs were mild (58.33%) or moderate (41.67%), with no severe cases observed. The DDDc of pentoxifylline was 143.4 yuan. Cost-effectiveness analysis demonstrated strong economic viability, with ICER values of 55.7 yuan per percentage point improvement in ulcer healing rate and 9.0 yuan per additional meter of pain-free walking distance, significantly below the willingness-to-pay threshold.Conclusion: Pentoxifylline demonstrates cost-effectiveness and manageable safety risks but has a low rational prescription rate, highlighting the need for improved clinical practices. Enhanced collaboration between pharmacists and medical staff, alongside stricter adherence to guidelines, is essential to optimizing its utilization.Keywords: pentoxifylline, special evaluation, adverse drug reactions, defined daily dose consumption, rational use